The potential of law in implementation of functions of the state in the scientific and technological sphere: Problems and prospects - L.A. Gumerov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The research has been performed with the purpose of forming scientifically grounded knowledge about the role of law in the regulation and implementation of the state's activities in the scientific and technological sphere. The main method used to achieve this goal has been the dialectical general philosophical method. In accordance with this method, structural-functional and logical methods, formal legal and comparative legal methods have been also applied. As a result of the research, it has been established that the main functions of the state in the sphere of relations under consideration are as follows: ensuring scientific and technological development; protecting scientific and technological potential. The examples given in the paper have made it possible to conclude that the potential of law in the implementation of the functions of the state in the scientific and technological sphere is not fully involved. Conflicts and contradictions in the norms of law have been revealed. Theoretical-methodological and practical problems related to the role of law in the performance of state functions in the scientific and technological sphere have been revealed. It has been established that integrative legal theory contributes to a fuller realization of the potential of law, as well as the need to adopt codifying rules of law. The practical significance and value of the work lies in the fact that its main provisions and conclusions can be used both in scientific and pedagogical activity and in drafting normative legal acts related to implementation of the functions of the state in the scientific and technological sphere.